ANIMAL REVOLT AND LINES OF FLIGHT IN LUCRETIUS, BOOK FIVE. (December 2020) - Hutchins, Richard
Abstract : Lucretius is the first classical author to have written a history of animal resistance. In a fifty-line passage from Book Five of De rerum natura, the 'animal revolt' (5.1297–349), Lucretius describes the rise of empire and its instrumentalization of animals for war. When the animals are led onto the battlefield, however, they swerve against their 'armed teachers and savage masters' (1311). The linear rise of empire, built on the abuse of animals' bodies, is deterritorialized by those same animal bodies in a chaotic scene that takes place on what Monica Gale has called a 'cosmic battlefield'. This paper follows Lucretius' account in Book Five of De rerum natura of the linear rise of empire, its increasing capture of animal life, and the rupture of empire's linear trajectory by a clinamen, or 'swerve', of rebel animals. I compare Lucretius' account of the rise of empire to what Deleuze and Guattari call a 'molar line', and the swerve of rebel animals to Deleuze and Guattari's notion of the 'line of flight'.